Analisis Sosiometri dalam Menggambarkan Dinamika Hubungan Sosial Mahasiswa Bimbingan dan Konseling di Universitas Sriwijaya - Argina Farenta; Annisa Rahman; Denisa Septiani; Mutia Najwa Khairunnisa; Novi Fayza Widi Putantri; Oktavia Utami Ramdhani; Okti Pravitasari; Sigit Dwi Sucipto (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2026)
This study aims to describe the dynamics of students’ social relationships using sociometric techniques within the context of guidance and counseling services. Social relationships are an essential aspect of individual development, particularly for guidance and counseling students who are expected to possess strong interpersonal skills as future counselors. This research employed a descriptive quantitative approach using a sociometric questionnaire covering aspects of collaborative learning, group work, understanding difficult materials, and emotional support. The participants consisted of 21 students from the Guidance and Counseling study program, selected using a total sampling technique. The data were analyzed using frequency distribution of peer selection and presented in the form of a sociometric matrix and sociogram to facilitate the interpretation of social interaction patterns within the group. The findings revealed that social relationships were not evenly distributed but tended to be concentrated on certain individuals. Some students demonstrated high levels of selection, indicating their role as central figures in both academic and emotional interactions, while others showed low levels of selection, suggesting potential social isolation. These findings indicate that group dynamics are influenced by social skills, academic competence, and individual empathy. Therefore, guidance and counseling services play a crucial role in improving the quality of students’ social interactions through appropriate interventions, such as group guidance and social skills training. This study is expected to serve as a foundation for developing more effective and inclusive guidance and counseling services.